Pendekatan Conjoint Analysis untuk Mengukur Tingkat Preferensi Mahasiswa terhadap Layanan Sistem Informasi Akademik di UIN Yogyakarta - Supandi, Epha Diana (Jurnal Fourier, 2012)
Information Technology (IT) represent one of main indicator to support the academic atmosphere at the university. Therefore UIN Sunan Kalijaga (Suka) Yogyakarta has owned sistem information technology and it is called Academic Information System (SIA). UIN Suka shall has knowledge preference and perception of consumer to the service, which is like what required by consumer. By using Conjoint Analysis method would have been obtained combination from level-level factor (stimuly) took a fancy by consumer according to value of highest utility from every level factor.Â  The objective of this research is to measure preference level of consumers (students) to the SIA services in UIN Suka used Conjoint Analysis method. The result shows that the most important factor in using SIA service is the benefit (importance value is 66,623%, the second important factor is accesibility of SIA ( importance value is 19,227%) and the last important is ability of staffÂ  (importance value is 14,15%). According to value of utility estimate, it shows that consumers like to use SIA for key in courses (utility estimate is 2,104), online service (utility estimate is 0,577) and SIA staff who are very friendly when they were servicing the students (utility estimate is 0,210).